Surgical outcomes of cable plate fixation in treatment of Vancouver type B1 and type C periprosthetic femoral fractures: a retrospective case series - Cengiz Şen; Taha Kızılkurt; Mehmet Demirel; Ahmet Müçteba Yıldırım; Yavuz Sağlam; İrfan Öztürk (Acta Orthopaedica et Traumatologica Turcica, 2024)
Objective: This study aimed to investigate the mid-to-long-term surgical outcomes of open reduction and internal fixation (ORIF) using a hybrid locking plate/cable technique for the treatment of Vancouver type B1 and type C periprosthetic femoral fractures (PPFs) in a consecutive group of patients from a single tertiary referral center.